2022
DOI: 10.3390/jof8111186
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Mechanism of Trichoderma virens-Induced Developmental Effects on Agrostis stolonifera Disease Resistance against Dollar Spot Infection

Abstract: Trichoderma is internationally recognized as a biocontrol fungus for its broad-spectrum antimicrobial activity. Intriguingly, the crosstalk mechanism between the plant and Trichoderma is dynamic, depending on the Trichoderma strains and the plant species. In our previous study, the Trichoderma virens 192-45 strain showed better pathogen inhibition through the secretive non-volatile and volatile substrates. Therefore, we studied transcriptional and metabolic responses altered in creeping bentgrass (Agrostis sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 86 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…VOCs, 2,4-di-tert-butylphenol and 4-methyl-1-pentanol, released by Aspergillus niger strain La2, are promising novel candidate biocontrol agents for the control of pear Valsa canker ( Shi et al, 2024 ). T. virens and its emitted metabolites, including linolenic acid, fumaric acid, and citric acid, were reported to possess antifungal activity and influence pathogen metabolism ( Gan et al, 2022 ). The metabolites are effective antifungal compounds that interfere with critical processes in target pathogens and enhance the competitive ability of biocontrol strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VOCs, 2,4-di-tert-butylphenol and 4-methyl-1-pentanol, released by Aspergillus niger strain La2, are promising novel candidate biocontrol agents for the control of pear Valsa canker ( Shi et al, 2024 ). T. virens and its emitted metabolites, including linolenic acid, fumaric acid, and citric acid, were reported to possess antifungal activity and influence pathogen metabolism ( Gan et al, 2022 ). The metabolites are effective antifungal compounds that interfere with critical processes in target pathogens and enhance the competitive ability of biocontrol strains.…”
Section: Discussionmentioning
confidence: 99%
“…The antibiosis mechanism involved in the interaction between Trichoderma and pathogen is driven by a variety of primary and secondary metabolites secreted by Trichoderma . These metabolites, including fatty acids, organic acids, terpenes, amides, and others ( Zhang et al, 2018 ; Gan et al, 2022 ; Zaid et al, 2022 ), have broad-spectrum antimicrobial activity in their ecological niches, can destroy cell membrane, and inhibit mycelium growth or spore germination of the targeted pathogen. A previous study showed that fermentation of Trichoderma longibrachiatum T6 could exert antifungal effects on the pathogen V. mali of apple Valsa canker, such as inhibiting conidia germination, altering mycelial morphology, and blocking growth ( Zhu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation